The Viking she would have married - Morris, Lucy (Harlequin historical, 2022)
With her family fallen on hard times, Valda's forced to join the crew on Halfdan Ulfsson's merchant ship as he sets sail on the treacherous silk route. But this handsome jarl's son is the man she'd planned to wed, until his bitter betrayal. Knowing she can never trust him, she must focus on saving her sisters...and not the intense connection that still burns between them!